Numerical experiments of two-phase flow in pipelines with a two-fluid compressible model - Loilier, P.; Omgba-Essama, C.; Thompson, Chris (Cranfield University, 2005)
Getting an accurate understanding of the dynamics of multiphase transport for the design of efficient pipelines is an important issue in the oil and gas industry. This paper presents simulations of one-dimensional two-phase flow in pipelines. The compressible model used is derived from the two-fluid model where pressure relaxation terms are added. The governing system consists of five time- dependent partial differential equations solved explicitly by a finite volume approach. Numerical results on well-known air-water compressible flow problems are performed and analysed. Common problems are observed with coarse meshes and are reduced with mesh refinement. We conclude that the model and the discretisation each behave well in regions of large discontinuities of pressure and velocities.